1973
DOI: 10.1172/jci107235
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Patterns of Triglycerides, Free Fatty Acids, Blood Sugar, and Insulin during Carbohydrate-Induction in Man and Their Modification by Nocturnal Suppression of Lipolysis

Abstract: A B S T R A C T Previous studies have shown that carbohydrate induction of hypertriglyceridemia in normal subjects occurs at night and appears to be related to a rise of free fatty acids after diurnal feeding of high-carbohydrate formula diet. The present investigation was undertaken to observe the effect on 24-h triglyceride, free fatty acid, blood sugar, and plasma insulin profiles of inhibition of nocturnal lipolysis by glucose or nicotinic acid in normal subjects and in patients with type IV hyperlipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
2

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(63 citation statements)
references
References 18 publications
4
56
1
2
Order By: Relevance
“…Overnight levels of FFA are thought to be important regulators of the response of fasting plasma triglycerides to a high carbohydrate diet (2). In fact, Shlierf et al demonstrated inhibition of carbohydrate-induced hypertriglyceridemia by overnight intravenous infusions of glucose, which suppressed nocturnal flux of FFA (32). In the three subjects studied, overnight plasma FFA levels did not differ during the two study periods.…”
Section: Discussionmentioning
confidence: 88%
“…Overnight levels of FFA are thought to be important regulators of the response of fasting plasma triglycerides to a high carbohydrate diet (2). In fact, Shlierf et al demonstrated inhibition of carbohydrate-induced hypertriglyceridemia by overnight intravenous infusions of glucose, which suppressed nocturnal flux of FFA (32). In the three subjects studied, overnight plasma FFA levels did not differ during the two study periods.…”
Section: Discussionmentioning
confidence: 88%
“…3). Human subjects show higher levels of plasma FFA at night due to enhanced lipolytic activity and this variation persists during fasting (Carroll and Nestel, 1973;Gibson et al, 1975;Schlierf and Dorow, 1973). When minimizing the indirect effects of calorie intake and sleep, by maintaining human subjects in constant dim light, feeding them with hourly isocaloric meals and keeping them awake for 40 hours, Dallmann et al (2012) reported a maintenance of rhythmic plasma FFA levels.…”
Section: Circadian Regulation Of Lipid Metabolism In Diurnal Mammalsmentioning
confidence: 99%
“…Whether this reflects true circadian control of meal lipid and carbohydrate handling or entrainment to a habitual sequence of meals is not clear. While there is some evidence to suggest circadian variation in postprandial lipid response (Reaven et al, 1988;Romon et al, 1997) and in plasma total TAG concentrations (Barter et al, 1971;Schlierf & Dorow, 1973;Rivera-Coll et al, 1994), the experimental designs of such studies do not exclude the possibility that such observations may reflect the frequency or macronutrient content of the test meals. Fielding et al (1996) and Evans et al (1998) reported appearance of fatty acids in TAG in a chylomicron-rich lipoprotein fraction following the second meal of a two-meal sequence which was suggested to result from incomplete mobilisation from the gut of TAG from the first meal.…”
Section: Discussionmentioning
confidence: 99%